Transcriptomic and metabolomic analysis of peri-tumoral hepatic tissue in hepatocellular carcinoma: unveiling the molecular landscape of immune checkpoint therapy resistance - Bi, Huaqiang; Feng, Kai; Wang, Xiaofei; Zheng, Ping; Qu, Chengming; Ma, Kuansheng (Frontiers in Pharmacology, 2024)
Background: Hepatocellular carcinoma (HCC) often resists traditional treatments, necessitating new therapeutic approaches. With immune checkpoint therapy emerging as a promising alternative, understanding its resistance mechanisms becomes crucial. Methods: Using 22 samples from 11 HCC patients, we conducted a comprehensive transcriptomic and metabolomic analysis of peri-tumoral hepatic tissues from those treated with Atezolizumab. Results: We identified significant metabolic alterations and a correlation between the COMMD3-BMI1 gene and Dephospho-CoA metabolite. Findings suggest these as potential markers for therapeutic resistance, as evidenced by upregulated COMMD3-BMI1 and downregulated Dephospho-CoA in non-responsive patients, with animal models further supporting these observations. Discussion: The study highlights COMMD3-BMI1 and Dephospho-CoA as critical actors in immune checkpoint therapy resistance in HCC, providing insights and potential pathways for more effective therapeutic strategies.